A Combination Rule for Portfolio Selection with Transaction Costs*. (9th June 2016) - Suh, Sangwon
Abstract: We propose a new portfolio rule for portfolio selection problems in the presence of transaction costs. The new portfolio rule is formed by combining an extant portfolio rule with the no‐rebalancing portfolio rule, which specifies the current portfolio weights before rebalancing as the desired portfolio weights. The new portfolio rule can be applied into most extant portfolio rules. Simulation and out‐of‐sample evidence show that the new portfolio rule can greatly improve portfolio performance, in comparison with the extant portfolio rules to be combined.